Moving Motion Control System On Developed Tripod Hopping Robot - Anuar , Mohamed Kassim; Mohammad Fahmi , Miskon; Nurul Hafizah, Abd Rahim; Takashi , Yasuno (2011)
This paper discussed on evaluation and validation of method in order to generate the moving motion control system of the developed tripod hopping robot. The proposed method to control the system is designed by using MATLAB&Simulink which consist of reference height control system and the networks of Central Pattern Generator (CPG) that can controlled the hopping height of each leg independently. By using this method, one of the legs of the tripod hopping robot is set to different value than the other leg in order to make the posture of hopping robot’s body incline ahead towards to the direction which it should move, respectively. As the result, the effectiveness of the approached method to generate moving motion of the hopping robot using CPG networks that including the reference height control system is confirmed while maintain the stability of developed tripod hopping robot from tumbled ahead.